Pyoderma gangrenosum: An ulcerative variant developing at a paraincisional LSCS scar site - Kritika Pandeyy; Mansak Shishak; Neeraj Yadav (Our Dermatology Online, 2021)
Pyoderma gangrenosum (PG) is an uncommon entity based on a diagnosis of exclusion. It can manifest itself mimicking various ulcerative cutaneous conditions and nonhealing wounds. With its less known etiology and presentation, there is a danger of mistreatment. Herein, we present an interesting case of pyoderma gangrenosum in a young woman, developing around the area of a lower segment Cesarean scar, but not involving the scar tissue. The PG was not associated with any underlying systemic ailments and responded well to a tapering dose of oral corticosteroids. Prompt diagnosis and initiation of therapy lead to a good response and favorable prognosis. Recognizing the atypical clinical presentations of PG is pertinent. Treatment with immunosuppressive agents and a multidisciplinary approach are recommended.